Status and correlates of attitudes towards end-of-life care among nursing students - Wejdan Othman Younis; Hamza Alduraidi; Ruqayya Seyyed Zeilani; Ayman Mohammad Hamdan-Mansour (Tehran University of Medical Sciences, 2022)
Background & Aim: Palliative nursing is based on the ability of nursing students to use their accumulated experiences and knowledge; however, basic nursing education does not provide adequate knowledge and skills regarding palliative and end-of-life care.  This study aimed to examine the relationship between knowledge of end-of-life care and attitudes toward dying people among nursing students.    Methods & Materials: Cross-sectional, descriptive-correlational design was used in this study. A total of 708 nursing students were recruited conveniently from nursing students in 11 nursing programs. Data was collected using an online self-administered questionnaire in relation to knowledge and attitudes regarding palliative care using the palliative care quiz for nursing and Frommelt Attitudes Toward Care of the Dying Scale Form B (FATCOD-B). Results: Nursing students have a satisfactory level of knowledge about palliative care with a mean of 61.0% and 50% of them scoring 83% correct answers. Moreover, students also have a moderate to high mean score (102.7, SD= 11.2) on attitudes towards caring for dying patients, indicating positive attitudes. Positive correlation found between communication and family as caregiver subscales of attitudes with knowledge total score (r= .08, r= .20, p< .05; respectively). The significant difference was found in attitudes related to gender, type of university, and whether receiving training or education about palliative care at school (p< .05). Conclusion: Attitudes of nursing students and improving the level of knowledge regarding end of life care should be a priority to nurse educators, and nursing schools need to integrate palliative and end-of-life care into nursing curricula across all levels.